PS1-04: Change in Adherence to Antiretrovirals After Initial Use of an Electronic Shared Medical Record Among HIV-infected Individuals - Silverberg, Michael (Marshfield Clinic, 2012)
BACKGROUND/AIMS: Patient web sites with shared medical records (SMR) allow patients to communicate with providers, view results of medical tests, refill prescriptions, and schedule appointments. We aimed to determine whether use of the SMR changed adherence to antiretroviral therapy (ART) in HIV-infected individuals. METHODS: We identified all HIV-infected adults who used the SMR one or more times within two years of initial rollout in two large integrated healthcare systems: Kaiser Permanente Northern California and Group Health Cooperative. The study population included enrollees with continuous membership during a 30-month period spanning 12 months prior to initial SMR use to 18 months after initial SMR use. The primary outcome was change in ART refill adherence comparing the 12-month period prior to initial SMR use with the 12-month period starting 6 months after initial SMR use to allow for SMR adoption; differences over time were evaluated by paired t-test. Next, using linear regression adjusted for age, sex, and health plan, we compared changes in adherence for users followed for at least 36 months after SMR rollout with changes for age- and sex-matched non-users over the same time span; non-users were assigned a random reference date. Finally, among users, we evaluated whether age, sex, race/ethnicity, HIV risk, health plan and an AIDS diagnosis influenced changes in adherence. RESULTS: We identified 1,663 HIV-infected SMR users during follow-up, including 1,475 users with 36 months follow-up after roll-out; 1,036 individuals who did not use the SMR during 36 months post rollout were also identified. Among users, mean adherence did not change before (90.4%) and after (90.2%) SMR use (P=0.52). In contrast, among non-users, mean adherence declined over time by 2% from 88% to 86% (P=0.001 compared with users). Among users, only sex of all factors evaluated was associated with changes in adherence with an increase of 2.5% for women and decrease of 0.4% for men (P=0.033). DISCUSSION: SMR users maintained adherence while non-users had small declines over time. Future studies should focus on amount of SMR use, longer-term effects, and identify additional subsets of patients that may particularly benefit from the enhanced access provided by SMR services.